ANALISIS KADAR LOGAM Pb, Mn dan KANDUNGAN PROTEIN PADA DAGING UDANG WINDU (Penaeus sp.) YANG DIAMBIL DIPERAIRAN SUNGAI DONDANG KECAMATAN MUARA JAWA - Octavianus, Riyan; Kartika, Rudi; Hindryawati, Noor (Jurusan Kimia FMIPA UNMUL, 2018)
Research on metal concentration of Pb, Mn and protein content in windu shrimp’s meat (Penaeus sp.) analysis in Dondang river, Muara Jawa have been done. This research is aimed to determine the concentration of heavy metal Pb, Mn and concentration of protein inside windu shrimp based by size and different sampling location. Concentration of heavy metal Pb, Mn and protein are correlated using Least Square method. Concentration of heavy metal Pb and Mn are analyzed by using AAS (Atomic Absorption Spectrophotometry) and concentration of protein are analyzed by using Kjeldahl method. Result of this research is the concentration heavy metal Pb and Mn in sampling point 1 in average concentration are 0.556 mg/L and 0.463 mg/L, sampling point 2 are 0.790 mg/L and 0.738 mg/L, sampling point 3 are 0.876 mg/L and 0.905 mg/L. Concentration of protein in windu shrimp in sampling point 1 in average are 23.4928%, sampling point 2 are 28.1701% and sampling point 3 are 29.1622%. Correlation of concentration of heavy metal Pb and Mn to the concentration of protein in windu shrimp (penaeus sp.) with R = 0.791; r = 0.948.